Study approach used by undergraduate occupational therapy students in Universiti Teknologi MARA (UiTM) Selangor./ Siti Nur Ain Mohamad and Kannan K. Thanapalan - Mohamad, Siti Nur Ain; Thanapalan, Kannan K. (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Studying in a post-secondary education environment involves conceptual changes. There are three approaches to studying which are the deep approach, strategic approach and surface approach. Type of study is important in acquiring knowledge given and needed for certain profession. Thus, valuable to identify the approaches used by students on it would help program to tailor annual effective delivery system and curricular review. This study was conducted to determine approaches used among undergraduate Occupational Therapy (OT) students. A cross-sectional study conducted involving 91 participants from semester four, semester six and semester eight of undergraduate OT in students UiTM Selangor, Puncak Alam Campus. All the participants need to answer a questionnaire that consist of Approaches and Study Skills Inventory for Students (ASSIST) short version was used to identify the tendencies of students to adopt approach to studying. 91 participants, 35% of students used deep approach (n=32), 33% used surface approach (n=30), and 32% used strategic approach (n=29). A Kruskal Wallis H test had determined that there are significant difference between the types of study approach and the demographic characteristic (level of study and age) (p<0.05). There are significant different between the mean of study approach with level of study and age of participant.